Ecological Analysis of Success of TB Treatment and Its Related Factors in Indonesia in 2019 (Medico Legal Update, 2021)
Background: Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium Tuberculosis).Indonesia is ranked third in the world, with the largest incidence of tuberculosis after China and India, with845,000 cases or 315/100,000 in 2019. The study was intended to analyze the coverage of treatment of allcases, the percentage of poor people by province and the ratio of public health centre per sub-district in theprovince to the success of tuberculosis treatment in all provinces in Indonesia in 2019.Methods: The ecological approach is carried out using secondary data from the Ministry of Health of theRepublic of Indonesia in the form of Health Profile of the Republic of Indonesia in 2019 and Data andInformation: Health Profile of Indonesia in 2019. Data from 34 provinces in Indonesia related to the successrate of TB treatment, the coverage of treatment of all TB cases, the percentage of poor people by provinceand the ratio of public health centre per sub-district in the province using cross tabulation.Results: The results showed that the success rate of TB treatment in Indonesia in 2019 was in the moderatecategory in line with the coverage of all TB cases, the percentage of poor people by province and the ratio ofpuclic health centre per sub-district in the province which is also in the moderate category.Conclusion: Efforts to monitor and record cases and treatment of TB patients need to be improved toimprove TB treatment coverage. Improving the economy of the community and equalizing the availabilityof public health centre are also very important to improve the success of TB treatment.